The MCRA toolbox of models and data to support chemical mixture risk assessment. (April 2020) - van der Voet, Hilko; Kruisselbrink, Johannes W.; de Boer, Waldo J.; van Lenthe, Marco S.; van den Heuvel, J.J.B. (Hans); Crépet, Amélie; Kennedy, Marc C.; Zilliacus, Johanna; Beronius, Anna; Tebby, Cleo; Brochot, Céline; Luckert, Claudia; et al.
Abstract: A model and data toolbox is presented to assess risks from combined exposure to multiple chemicals using probabilistic methods. The Monte Carlo Risk Assessment (MCRA) toolbox, also known as the EuroMix toolbox, has more than 40 modules addressing all areas of risk assessment, and includes a data repository with data collected in the EuroMix project. This paper gives an introduction to the toolbox and illustrates its use with examples from the EuroMix project. The toolbox can be used for hazard identification, hazard characterisation, exposure assessment and risk characterisation. Examples for hazard identification are selection of substances relevant for a specific adverse outcome based on adverse outcome pathways and QSAR models. Examples for hazard characterisation are calculation of benchmark doses and relative potency factors with uncertainty from dose response data, and use of kinetic models to perform in vitro to in vivo extrapolation. Examples for exposure assessment are assessing cumulative exposure at external or internal level, where the latter option is needed when dietary and non-dietary routes have to be aggregated. Finally, risk characterisation is illustrated by calculation and display of the margin of exposure for single substances and for the cumulation, including uncertainties derived from exposure and hazard characterisation estimates. Graphical abstract: Image 1 Highlights: MCRA is a modular model and data toolbox to assess combined chemical exposure risks. Substances can be selected based on adverse outcome pathway networks or QSAR models. Benchmark doses and relative potency factors with uncertainty can be calculated. Kinetic models can be used for in vitro to in vivo extrapolation or for aggregation. Risks can be assessed through traditional or probabilistic margins of exposure.